2009
DOI: 10.1088/0004-637x/693/1/564
|View full text |Cite
|
Sign up to set email alerts
|

2006 Whole Earth Telescope Observations of Gd358: A New Look at the Prototype DBV

Abstract: We report on the analysis of 436.1 hrs of nearly continuous high-speed photometry on the pulsating DB white dwarf GD358 acquired with the Whole Earth Telescope (WET) during the 2006 international observing run, designated XCOV25. The Fourier transform (FT) of the light curve contains power between 1000 to 4000 µHz, with the dominant peak at 1234 µHz. We find 27 independent frequencies distributed in 10 modes, as well as numerous combination frequencies. Our discussion focuses on a new asteroseismological analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…The lack of known white dwarf planets is gaining statistical significance and further timing observations of pulsating white dwarfs could place strong constraints on post-main-sequence stellar evolution. Sullivan et al (2008) identified the frequency of A to be an additive combination of the frequencies of E and G, a well-known occurrence in white dwarf pulsators (see, e.g., Provencal et al 2009). Any perturbation to the frequency of E or G should result in an identical perturbation to the frequency of A.…”
Section: Planetary Detection With the Pulsation Timing Methodsmentioning
confidence: 99%
“…The lack of known white dwarf planets is gaining statistical significance and further timing observations of pulsating white dwarfs could place strong constraints on post-main-sequence stellar evolution. Sullivan et al (2008) identified the frequency of A to be an additive combination of the frequencies of E and G, a well-known occurrence in white dwarf pulsators (see, e.g., Provencal et al 2009). Any perturbation to the frequency of E or G should result in an identical perturbation to the frequency of A.…”
Section: Planetary Detection With the Pulsation Timing Methodsmentioning
confidence: 99%
“…A phenomenon reminiscent of these outburst-like events was the sforzando event detected in 1996 for the DBV GD358, in which the star dramatically altered its pulsation characteristics on a timescale of hours(Provencal et al, 2009). …”
mentioning
confidence: 99%
“…The most famous example is the so-called sforzando effect observed in GD 358. This star showed a high-amplitude sinusoidal light variation for a short period of time instead of the non-linear variability observed just a day before (Kepler et al 2003;Provencal et al 2009). To explain the short-term changes in the pulsational behaviour of a star is challenging.…”
Section: Introductionmentioning
confidence: 79%